The Philosopher : A History in Six Types - Smith, Justin E. H. (Book collections on Project MUSE., 2016)
"What would the global history of philosophy look like if it were told not as a story of ideas but as a series of job descriptions--ones that might have been used to fill the position of philosopher at different times and places over the past 2,500 years? The Philosopher does just that, providing a new way of looking at the history of philosophy by bringing to life six kinds of figures who have occupied the role of philosopher in a wide range of societies around the world over the millennia--the Natural Philosopher, the Sage, the Gadfly, the Ascetic, the Mandarin, and the Courtier. The result is at once an unconventional introduction to the global history of philosophy and an original exploration of what philosophy has been--and perhaps could be again. By uncovering forgotten or neglected philosophical job descriptions, the book reveals that philosophy is a universal activity, much broader--and more gender inclusive--than we normally think today. In doing so, The Philosopher challenges us to reconsider our idea of what philosophers can do and what counts as philosophy"--Provided by publisher.